Nexus between Foreign Direct Investment, Energy Consumption, Natural Resource, and Economic Growth in Latin American Countries - Zeeshan, Muhammad; Han, Jiabin; Rehman, Alam; Bilal, Hazrat; Farooq, Naveed; Waseem, Muhammad; Hussain, Arif; Khan, Muhammad; Ahmad, Ilyas (International Journal of Energy Economics and Policy, 2020)
Most of the Latin American Countries have witnessed high economic growth in the last few decades. FDI is a key factor in achieving the exponential economic prosperity in these countries. Besides, the positive effect on Economic growth, it also contributes to energy consumption and helps in the extraction of natural resources to the host country. This study examines the nexus between FDI, energy consumption, natural resource, and economic growth in Latin American countries for the period of 1990 to 2018. We apply Structural Equation Modelling approach to examine the relationship among these variables. The empirical results suggest that FDI, Energy consumption and Natural resources have significant and positive association with Economic growth in Latin American countries. Likewise, FDI and Energy consumption also show positive and significant effect on Natural resource, while FDI show a positive and statistically significant effect on Energy consumption. The results imply that to fuel the fast-paced economic growth, the respective governments in these countries need to reform their energy sectors by tapping renewable energy resources and deploy green technologies with a view to avoid environmental degradation. In addition, respective government in this region should formulate robust business strategies and environment to encourage FDI inflow. Keywords: FDI, Energy Consumption Natural, Resource, Economic development Latin American Countries JEL Classifications: Q1, Q2, Q3, O13 DOI: https://doi.org/10.32479/ijeep.10255